Pengaruh Pemberian Buah Pepaya Terhadap Nafsu Makan Anak Berumur 2-5 Tahun di Wilayah Kerja Puskesmas Kuranji: Effect of Giving Papaya Fruit on Appetite Children Aged 2-5 Years in the Working Area of the Kuranji Health Center - Lili Fajria; Mitriya Rika (NERS Jurnal Keperawatan, 2013)
The appetite is a desire or urge to eat due to hunger. Appetite disorder is often experienced by toddlers. They are often picky food and easily exposed to infectious diseases so that experiencing malnutrition. For this reason, it needs an effort to overcome eating disorders for toddlers through nutritious therapy which is rich in vitamins, mineral and can make digestive system better. Papaya is rich in nutrion that can improve the appetite of toddlers. The purpose of this research is to know the influence of consuming 1 piece of papaya a day for a month to increase appetite of toddlers at Korong gadang posyandu, puskesmas kuranji ( kuranji community health centre ) working area 2012.The writer had 20 toddlers who are losing weight for the last one month for sampling. The research has been done since February 4th until March 5th 2012. The writer applied quantitative experiment one group pre-test design without control group. The toddlers are weight by using digital scale. The writer applied T-pair test for the statistic test. The result showed that there is a great increasing in toddler’s appetite. We can see it through the toddler’s weight scale after the intervention (=o 0,000). Based on the results of the research, the writer suggests puskesmas kuranji to promote society to consume 1 piece of papaya per day as nutritious therapy for the toddlers who have appetite disorder.